STUDI PEMANFAATAN LEMBO RUMAH UNTUK PENINGKATAN EKONOMI MASYARAKAT DI DESA MENCIMAI KECAMATAN BARONG TONGKOK KABUPATEN KUTAI BARAT - Hutiq, Katarina; Ismail, Ismail; Yahya, Zuhdi (Universitas 17 Agustus 1945 Samarinda, 2013)
The average total income of Respondents. Rp 3.080.000. Every month from the average income of Primary Works Rp. 2.070.000. and the average income of part time job. Rp 1.165.384. Every month. Income from Lembo Rumah can increase the average income of Rp. 1.097.200. Every month with 35.62% percent / household / month. This shows that Lembo Rumah can increase economic income of family in the village of Mencimai.